EVALUATION OF CARCASS CHARACTERISTICS, AND HEAMATOLOGICAL INDICES OF BROILERS FED DIETS SUPPLEMENTED WITH NEEM LEAF (AZADIRACHTAINDICA) MEAL IN COLD AND HOT SEASONS OF KEBBI STATE SUDAN SAVANNA - Ribah, Mohammed Ibrahim; Bawa, Aminu; Suleiman, Bello; Misbau , A Muftau (Research Journal of Agriculture (RJA), 2025)
Two feeding trials were conducted in the cold and hot seasons of 2023/2024, involving 144 unsexed day-old broiler chicks each, to determine the optimum level of supplementation of Neem Leaf Meal (NLM) in broiler diets in cold and hot seasons. The experiment was conducted in a completely randomized design (CRD). The birds were randomly allocated to four treatment groups of thirty-six birds per treatment; each treatment was replicated three times with 12 birds per replicate. The four groups were randomly allocated to four diets containing varying levels of NLM of 0, 3, 6, and 9% representing diets 1 to 4, respectively. At the end of the experiment, carcass characteristic and hematological indices were determined. Result on carcass characteristic shows no significant difference (P>0.05) in all the parameters measured, except for the weight of the feather, shank, and liver, which increased with the increase level of NLM. The result of hematological indices shows no significant difference (P>0.05) except in eosinophils, HP, MCH, and platelets. The second phase of the experiment, which was conducted in the hot season, indicated that both carcass characteristics and hematological indices were not significantly affected (P>0.05) by NML in all the parameters measured, except carcass weight. Hematological values were within the reference range. The results of the t-test only showed a significant (P<0.05) difference in the carcass characteristics of broilers supplemented with NLM in relation to the season. The result of hematological indices of broiler also shows no significant effect (P>0.05) when supplemented with NLM with relation to seasons. NLM supplementation should be adopted in the cold season in an inclusion of up to 9% for broiler production because it has been shown to influence carcass weight without showing a deleterious effect on the hematological characteristics of the birds.